2018
DOI: 10.1111/jfb.13849
|View full text |Cite
|
Sign up to set email alerts
|

Colours and colour vision in reef fishes: Past, present and future research directions

Abstract: Many fishes, both freshwater or marine, have colour vision that may outperform humans. As a result, to understand the behavioural tasks that vision enables; including mate choice, feeding, agonistic behaviour and camouflage, we need to see the world through a fish's eye. This includes quantifying the variable light environment underwater and its various influences on vision. As well as rapid loss of light with depth, light attenuation underwater limits visual interaction to metres at most and in many instances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 180 publications
(389 reference statements)
2
74
0
Order By: Relevance
“…This data also supports anatomical studies, which found high rod‐to‐cone ratios in the retinas of several members of this family (Fishelson et al, ). However, we also found a high diversity in cone opsin expression between species, which ranged in expression from two to six cone opsin genes, similar in number to diurnal reef fishes (reviewed in Marshall et al, and Losey et al, for MSP data).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…This data also supports anatomical studies, which found high rod‐to‐cone ratios in the retinas of several members of this family (Fishelson et al, ). However, we also found a high diversity in cone opsin expression between species, which ranged in expression from two to six cone opsin genes, similar in number to diurnal reef fishes (reviewed in Marshall et al, and Losey et al, for MSP data).…”
Section: Discussionsupporting
confidence: 58%
“…They all live in the same water type (Jerlov, ) over a similar depth range and feed against and in many cases on similarly coloured objects (e.g., coral, algae, turf‐algae or sand‐substrate). The variation seen in spectral sensitivity must be explained by other factors (Marshall et al, ), including environmental or behavioural ones. Finer‐scale habitat choice (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, competition for shelter may drive microhabitat partitioning in this family, with those forced into the open needing to develop other means of protection. Indeed, several species generally found in microhabitats away from structure (microhabitat A and B), such as R. gracilis , Z. viridiventer , T. zosterophora or Z. leptacantha , are of silvery‐translucent or pale appearance, providing excellent camouflage when viewed against a blue water background (Marshall, Cortesi, de Busserolles, Siebeck, & Cheney, ; Marshall & Johnsen, ). These species also form large schools, possibly further reducing predation risk (Pitcher, ).…”
Section: Discussionmentioning
confidence: 99%
“…All of the species appear to have red-shifted visual systems hinting towards the importance of 368 detecting longer-wavelengths of light for survival. Mounting evidence suggests that long-369 wavelength reception in coral reef fishes is especially beneficial when feeding on algae or 370 similar chlorophyll containing organic matter, which strongly reflect the red part of the light 371 spectrum (for a recent review on the topic see Marshall et al 2018). It is also possible that the 372 red-orange dorsal fin that appears unique to the terrestrial species (TJ Ord, unpublished data) 373 has evolved to exploit the pre-existing (ancestral) visual state of seeing red as a means of maximizing the efficiency of territorial and courtship signalling on land (Bhikajee and Green 375 2002, Shimizu et al 2006, Ord and Tonia Hsieh 2011.…”
mentioning
confidence: 99%